ANALISIS STRATEGI PENGEMBANGAN USAHA UCOK DURIAN MEDAN - I Imsar (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this study was to analyze the influential strategies in the development of Ucok Durian's business. In this study, there were several strategies that were carried out in the preparation of research. Program development strategies to determine and achieve company goals and implement their mission. The type of this research is descriptive research with qualitative approach, using SWOT analysis method, analysis made to know the strength, weakness (weakness), opportunity (opportunity) that open to company and some threats (Treath) which is identified. From the results of research based on interviews found that durian shoot is a strategy ranging from improving product quality, determine the characteristics of the product, and also determine the model dansu of the products it sells. In the price, Durian pricing sets the price starting from positioning the product through price and quality and also setting price and benefit for the consumer. At the strategy stage, Durian idioms choose places ranging from choosing a strategic location, a comfortable place, and meeting places for consumer convenience. In the promotion strategy, Durian urges a promotional strategy ranging from founders of billboards or banners, installing branding, mascots and slogans, and using social media for online promotion. Based on SWOT Analysis, durian ucok business has weakness (Weaknesses) that is promotion that is not used specifically, do not use technology, and goods are sold only one product. However, the durian cuttings still have strength (Strenght) to improve the condition. To develop businesses that need to be done is to maintain product quality, increase service, and increase product sales.